2000
DOI: 10.1209/epl/i2000-00203-9
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-solid transition of Laponite suspensions at very low ionic strength: Long-range electrostatic stabilisation of anisotropic colloids

Abstract: We study suspensions of synthetic clay Laponite at very low ionic strength. We show the existence, for these charged disk-like particles, of a liquid-soft solid transition mainly driven by electrostatic repulsive interactions. Such a process defines a re-entrant transition line in the phase diagram. Location of this line is predicted using basic arguments. The structure is characterized by ultra-small-angle X-ray scattering (USAXS). Soft-solid suspensions show a correlation peak compatible with long-range elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
209
3
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(227 citation statements)
references
References 23 publications
14
209
3
1
Order By: Relevance
“…These repulsions originate from the strong surface charges at the faces of the colloidal disks, making that the effective volume fraction is very high. Recent experiments have shown that the location of the "glass transition" line in the (volume fraction / electrolyte concentration) phase diagram is consistent with this assumption [17].…”
Section: Preparation and Viscometrymentioning
confidence: 71%
“…These repulsions originate from the strong surface charges at the faces of the colloidal disks, making that the effective volume fraction is very high. Recent experiments have shown that the location of the "glass transition" line in the (volume fraction / electrolyte concentration) phase diagram is consistent with this assumption [17].…”
Section: Preparation and Viscometrymentioning
confidence: 71%
“…Numerous investigations have been addressed to define the state diagram of aqueous Laponite dispersions in the ionic strength vs clay concentration plane, i.e. to individuate the different regions of isotropic liquids, disordered (gels and glasses), ordered (nematic phases), flocculated states (Cummins, 2007;Gabriel, Sanchez, & Davidson, 1996;Jabbari-Farouji, Tanaka, Wegdam, & Bonn, 2008;Levitz, Lécolier, Mourchid, Delville, & Lyonnard, 2000;Mourchid, Lécolier, Van Damme, & Levitz, 1998;Mourchid, Delville, Lambard, Lécolier, & Levitz, 1995;Mongondry, Tassin, & Nicolai, 2005;Ruzicka, Zulian, & Ruocco, 2004;Ruzicka, Zulian, & Ruocco, 2006;Tanaka, Meunier, & Bonn, 2004;Tanaka, Jabbari-Farouji, Meunier, & Bonn, 2005). The various contradictions emerging from the comparison of the proposed Laponite dispersion state diagrams are partly apparent and can be mainly ascribed to different aging times and, secondarily, to different protocols of samples preparation or Laponite type .…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence for such a Wigner glass at low electrolyte concentrations came from the rheological measurements of Rand et al 44 and from many other experiments. 10,13,25,45 By contrast, it has recently been hypothesized that Laponite suspensions could behave like an attractive glass. 17 A comprehensive discussion of different possible glassy states in Laponite suspensions, including comparison with experimental data, was recently given by Mongondry et al 46 and Tanaka et al 15,17 The majority of clay gelation studies have been done with Laponite suspensions due to their relatively high longitudinal monodispersity in comparison with natural clays.…”
Section: Introductionmentioning
confidence: 99%